PENGEMBANGAN KARAKTER DAN PENGUASAAN KONSEP DENGAN PENDEKATAN INQUIRY LABORATORY MATERI IDENTIFIKASI ALGAE - Rivanna Citraning Rachmawati; Eko Retno Mulyaningrum; Fenny Roshayanti . (Universitas PGRI Semarang, 2014)
CHARACTER DEVELOPMENT USING LABORATORY INQUIRY APPROACH IDENTIFY OF ALGAE MATERIAL ?é?áABSTRACT Student of class A II has the academic potential of above average compared to other classes. But on the other hand, the ability of the students during the practical is very slow, and the ability of students in the identification of preparations is lacking. Through monitoring and observation, the researchers also see the curiosity and hard work of each individual student is less. Learning through Inquiry approach is expected value of the individual characters e.g. discipline, curiosity, honesty, hard work and tolerance develop. The objective of the study is to determine of increasing character of the individual and the level of understanding of algae material. This study uses classroom action research in two cycles. Data collection techniques using character observation with rating scale sheets. The results showed an increase in the character of the individual student. The score of mastery learning in classical reached 94.7 %. So, the indicator has achieved ?óÔÇ??Ñ 75% on research success. Based on the results of this study concluded that there is an increased individual character and the students of biology education?óÔé¼Ôäó material understanding in Plant Taxonomy 1 learning through inquiry approach Key words: students?óÔé¼Ôäó individual character, inquiry approach, classroom action research ?é?áABSTRAK Mahasiswa kelas II A IKIP PGRI Semarang memiliki potensi akademik di atas rata-rata dibandingkan dengan kelas yang lain. Namun di sisi lain, kemampuan mahasiswa selama praktikum sangat lambat, dan kemampuan mahasiswa dalam identifikasi preparat sangatlah kurang. Melalui pengamatan dan observasi, kami juga melihat rasa ingin tahu, kejujuran, kerja keras dan toleransi dapat berkembang. Tujuan dari penelitian adalah untuk mengetahui peningkatan karakter individu dan tingkat pemahaman materi algae. Jenis penelitian ini menggunakan Penelitian Tindakan Kelas dengan 2 siklus. Teknik pengumpulan data menggunakan teknik observasi karakter dengan lembar rating scale. Hasil penelitian menunjukkan peningkatan karakter individu mahasiswa. Nilai ketuntasan belajar secara klasikal mencapai 94,7%, sehingga telah mencapai ?óÔÇ??Ñ 75% indikator keberhasilan penelitian secara klasikal. Berdasarkan hasil penelitian dapat disimpulkan bahwa ada peningkatan karakter individu dan pemahaman materi mahasiswa Pendidikan Biologi dalam praktikum Taksonomi Tumbuhan 1 melalui pembelajaran dengan pendekatan inquiry. Kata kunci: karakter individu mahasiswa, pendekatan?é?á inquiry, PTK